Plato’s Philosopher Rulers: Lessons for Nigeria - Ishmael Gwunireama; Moses Njobuawu Omah (dialektika kontemporer, 2021)
The current state of affairs in Nigeria is the reality of the state of nature portrayed by social contract philosophers. The Nigerian state has failed to provide security for lives and property. The basic necessities of life are luxuries in Nigeria. The legislators enact selfish laws while the judiciary is being emasculated by the mighty and the executive formulates and implements self-serving policies. The government has become of men rather than of laws. This is due to the failure of leadership, which is predicated on the quality of the rulers, most of whose level of education cannot afford them the acumen for statecraft. The matrices of the problem are: colonist influence; manipulations by the cult of the uneducated; and the political aloofness of educated Nigerians. Plato’s political ideology for an ideal state remains a classic reference for many generations after his death. In the instant case, his theme on the qualifications of the philosopher rulers (guardians) after rigorous educational training could serve as a paradigm for Nigeria. Therefore, the work recommends that the minimum educational qualifications for Nigerian rulers be reviewed upward to a university degree, which not only equates with the rigorous educational training for the guardians in Plato’s ideal state but also sufficient to broaden the horizons of the rulers to comprehend, analyse and reach decisions on complex issues. Thus, ss. 131 (d), 177 (c) of the CFRN 1999 (as amended) should be amended. Finally, educated citizens should be involved in the political affairs of Nigeria in order to fill the quality gap in the quality of rulers. Or else there would always be square pegs in round roles and the ship of state would wreck.